2020
DOI: 10.1186/s12864-019-6443-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analyses of cassava Pathogenesis-related (PR) gene families reveal core transcriptome responses to whitefly infestation, salicylic acid and jasmonic acid

Abstract: Background: Whiteflies are a threat to cassava (Manihot esculenta), an important staple food in many tropical/ subtropical regions. Understanding the molecular mechanisms regulating cassava's responses against this pest is crucial for developing control strategies. Pathogenesis-related (PR) protein families are an integral part of plant immunity. With the availability of whole genome sequences, the annotation and expression programs of the full complement of PR genes in an organism can now be achieved. An unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 83 publications
2
37
2
Order By: Relevance
“…Our results showed that the AM fungus improved the resistance of plants to pathogens by regulating PR proteins, since the expression of their genes was upregulated. It was worth noting that JA and SA can induce PR protein-related gene expression in plants (Irigoyen et al, 2020). The upregulation of the genes for PR proteins in AM plants is linked with the higher concentrations of JA and SA in the plant shoots.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the AM fungus improved the resistance of plants to pathogens by regulating PR proteins, since the expression of their genes was upregulated. It was worth noting that JA and SA can induce PR protein-related gene expression in plants (Irigoyen et al, 2020). The upregulation of the genes for PR proteins in AM plants is linked with the higher concentrations of JA and SA in the plant shoots.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that cassava responds to (U)CBSV infection with increased expression of genes belonging to the pathogenesis‐related (PR) gene family (Amuge et al, 2017; Anjanappa et al, 2018; Irigoyen et al, 2020). PR proteins are frequently used as biomarkers for defence signalling pathways and are associated with increases in plant hormones such as salicylic acid (SA) (Ali et al, 2018).…”
Section: Possible Roles For Viral Ham1mentioning
confidence: 99%
“…PR5 has been shown to be induced in response to salt and drought stress [ 21 ]. The results from Gene Ontology analysis demonstrate gene networks linked to SA are increased in response to DMN and previous research has shown that SA and Jasmonic acid alter the expression of PR proteins [ 22 ]. Thus, DMN may be functioning through this SA signaling mechanism in potato tubers to induce the drought associated protein PR5.…”
Section: Discussionmentioning
confidence: 98%